Movement Pattern of Scapular Dyskinesis in Symptomatic Overhead Athletes - Tsun-Shun Huang (Nature Portfolio, 2017)
Abstract This study investigated the characteristics of arm elevation via principal component analysis in symptomatic overhead athletes with scapular dyskinesis. One hundred-thirty-four overhead athletes with scapular dyskinesis [24: inferior angle prominence (pattern I); 46: medial border prominence (pattern II), 64: pattern I + II] were evaluated by three-dimensional electromagnetic motion and electromyography to record the scapular kinematics (upward rotation/posterior tipping/exterior rotation) and muscle activation (upper trapezius: UT; middle trapezius: MT; lower trapezius: LT; serratus anterior: SA) during lowering phase of arm elevation. The results showed: (1) for pattern I and II, the first 3 principal component (PCs) explained 41.4% and 42.6% of total variance of movement; (2) the first PCs were correlated with MT, LT activity (r = 0.41~0.61) and upward rotation, posterior tipping (r = −0.59~−0.33) in pattern I, and UT, MT, SA (r = 0.30~0.70) activity in pattern II; (3) contour plots of muscle activity demonstrated that muscle activities varied with dyskinesis patterns. In summary, for the pattern I, the major characteristics are coactivation of MT and LT and corresponding scapular posterior tipping and upward rotation. For the pattern II, the major characteristics are coactivation of UT, MT and SA without corresponding scapular external rotation.